1997
DOI: 10.1021/bi9620215
|View full text |Cite
|
Sign up to set email alerts
|

Positioning the Acid/Base Catalyst in a Glycosidase:  Studies with Bacillus circulans Xylanase

Abstract: The mechanism of action employed by a glycosidase is dictated, in part, by the distance between the two catalytic carboxylic acids. In the retaining endo-beta-1,4-xylanase from Bacillus circulans, this critical distance (approximately 5.5 A) has been altered by mutagenesis of the putative acid/base catalyst Glu172. An increase in the separation (Glu172Asp) resulted in a 400-fold decrease in the k(cat) value for xylan hydrolysis. By contrast, a decrease in the separation, achieved by the selective carboxymethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
79
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 27 publications
7
79
0
Order By: Relevance
“…Another conserved glutamic acid residue identified in a conserved motif of [G-(T/F)-E*] was also recognized as acid-base residue catalysts in the BLAST search comparing twelve known GH-12 cellulase sequences performed [73]. Comparisons with other retaining glycosidases revealed that a general acid-base catalytic mechanism is less consistent compared with a nucleophile catalytic mechanism [75,76]. Both the nucleophile conserved sequence (E*-(L)-M-(I)-W) and the acid-base residues sequence (G-(T)-E*) have been detected in cloned celB (amino acid residues 178-182 and 244-246, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Another conserved glutamic acid residue identified in a conserved motif of [G-(T/F)-E*] was also recognized as acid-base residue catalysts in the BLAST search comparing twelve known GH-12 cellulase sequences performed [73]. Comparisons with other retaining glycosidases revealed that a general acid-base catalytic mechanism is less consistent compared with a nucleophile catalytic mechanism [75,76]. Both the nucleophile conserved sequence (E*-(L)-M-(I)-W) and the acid-base residues sequence (G-(T)-E*) have been detected in cloned celB (amino acid residues 178-182 and 244-246, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…BCX has been the subject of much previous study using a variety of techniques including X-ray crystallography, NMR spectroscopy, and mutational analysis, leading to a well-defined structure and enzymatic mechanism, 12,13 including the identification of structural elements critical to cleavage of xylan substrates. [14][15][16][17][18] Despite the extensive characterization of BCX, previous attempts to characterize its folding kinetics using thermal denaturation failed due to aggregation upon unfolding; 4 attempts using chemical denaturation have encountered only limited success. 17,19 Because aggregation is highly dependent on protein concentration, refolding under dilute conditions has been used to alleviate such problems.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] Despite the extensive characterization of BCX, previous attempts to characterize its folding kinetics using thermal denaturation failed due to aggregation upon unfolding; 4 attempts using chemical denaturation have encountered only limited success. 17,19 Because aggregation is highly dependent on protein concentration, refolding under dilute conditions has been used to alleviate such problems. 4,20 In principle, if the concentration of unfolded proteins is sufficiently low, the rate of association between unfolded protein molecules (a second-order process) becomes slower than the rate of refolding (typically a first-order process), eliminating the possibility of aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Bacillus circulans xylanase (BcX) is a ∼20 kDa retaining endo-1,4-β-xylanase of the glycoside hydrolase family 11, clan GH-C †. 16 The enzyme has been extensively characterized kinetically, [17][18][19][20][21] as well as structurally by X-ray crystallography and NMR spectroscopy. [22][23][24] The β-sandwich protein has a fold resembling that of a partially closed right hand, with the active site "palm" formed by the cleft between the "fingers" and "thumb".…”
Section: Introductionmentioning
confidence: 99%